SUPPORTIVE COMMUNICATION IN THE PROGRAM FOR HANDLING VIOLENCE AGAINST MUSLIM CHILDREN AT DP3AP2KB BOGOR - Ainun Nafisah; Ellys Lestari Pambayun (Department Islamic Education, Faculty of Education and Teacher Traning, Universitas Islam Bandung, 2026)
This study aims to explore the implementation of supportive communication in programs addressing violence against Muslim children at DP3AP2KB in Bogor Regency. Using the theoretical foundations of Burleson and MacGeorge as well as Jack Gibb's supportive behaviors, this study analyzes the integration between universal psychological techniques and Islamic spiritual education. The research results show that DP3AP2KB implements the